Quality of nursing work life and job stress among nurses working in inpatient units - Suci Melani, Poppyana; Mawarti, Indah; Yuliana, Yuliana; Yusnilawati, Yusnilawati; Andini, Febri Tri (JOURNAL OF Mental Health Concerns, 2025)
Background: Quality of Nursing Work Life (QNWL) plays an important role in maintaining nurses' performance in the quality of health services. If QNWL is low, this can increase job stress, thereby reducing the quality of care and nurses' performance. Purpose: To determine the relationship between quality of nursing work life and job stress among inpatient nurses. Method: A quantitative study. The design was analytical with cross sectional, the research sample consisted of 46 nursing inpatients at Arafah Islamic Hospital, Jambi City. Data was collected using a validated questionnaire. Data analysis included univariate analysis, normality test with Shapiro-wilk, and bivariate analysis with spearman rank correlation. Results: Based on the results of the Spearman rho statistical test, it shows that the overall sub-variables of quality of nursing work life and job stress have a significant relationship with a p-value (<0.05). Conclusion: It is important for nurses to maintain a balance in the quality of their work in healthcare services. A good quality of nursing work life will result in maximum improvement in work quality. The better the quality of nursing work life, the lower the level of job stress experienced. Keywords: Healthcare Service; Inpatient; Nurses; Quality of Nursing Work Life; Job Stress.